Lignin-based sulfur-oxygen-doped porous carbon adsorbent as well as preparation method and application thereof

By mixing lignin with potassium thiosulfate for ball milling and high-temperature carbonization activation treatment, lignin-based sulfur-oxygen doped porous carbon adsorbent was prepared, which solved the problem of insufficient specific surface area and pore capacity of traditional adsorbents, and achieved efficient Simplification of dye wastewater treatment and preparation process.

CN119430177AInactive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411460370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, traditional adsorbents have problems with insufficient specific surface area and pore capacity when treating dye wastewater, resulting in poor adsorption performance and complex chemical activation process, which increases the preparation cost.

Method used

By mixing lignin with potassium thiosulfate for ball milling, followed by high-temperature carbonization activation treatment, one-step activation and doping were achieved, and a lignin-based sulfur-oxygen doped porous carbon adsorbent was prepared.

Benefits of technology

The specific surface area and pore volume of the adsorbent are significantly improved, the adsorption capacity and removal rate of methylene blue are enhanced, the preparation process is simplified, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430177A_ABST
    Figure CN119430177A_ABST
Patent Text Reader

Abstract

The invention relates to a lignin-based sulfur-oxygen-doped porous carbon adsorbent as well as a preparation method and application thereof. According to the method, lignin is used as a carbon source, potassium thiosulfate is used as a sulfur-oxygen doping agent and an activating agent, a novel lignin activation technology is provided, lignin and K2S2O3 are subjected to ball milling and mixing according to a specific mass ratio, and then the mixture is calcined into carbon in a tubular furnace under nitrogen gas flow; the preparation method solves the problem of mixed activation side reaction of an activator and a heteroatom dopant in traditional chemical activation, realizes one-step activation and doping preparation of porous carbon, is simple in preparation process and low in equipment requirement, can effectively reduce the production and preparation cost, and is suitable for industrial large-scale production. The specific surface area of the prepared lignin porous carbon adsorbent can reach 3301 m < 2 > / g, the total pore volume can reach 2.33 cm < 3 > / g, and the pore volume of mesopores accounts for 80%. In performance application, the adsorption capacity to methylene blue reaches 1122mg / g, and meanwhile, the composite material has the specific capacitance of 250F / g under 1M KOH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparing high-quality carbon materials from biomass, and specifically relates to a lignin-based sulfur-oxygen doped porous carbon adsorbent and a preparation method and application thereof. Background Art

[0002] Today, removing synthetic dyes from industrial water remains one of the industrial challenges of environmental governance. Surveys show that about 80% of dye-containing wastewater is discharged into rivers and seas without treatment, causing adverse effects on the ecosystem on which human beings depend for survival.

[0003] In actual wastewater treatment, although traditional physical treatment, chemical treatment, biological treatment and membrane separation technologies are effective, their technology, equipment and labor costs have also risen accordingly. Adsorption has the advantages of simple operation, low cost and no secondary pollution, and is an effective means to treat dye wastewater. However, the adsorbent requires a larger specific surface area and pore volume to provide more adsorption sites and channels. In addition, good physical and chemical stability can enable the adsorbent to maintain its adsorption performance under different environments. Therefore, carbon adsorbents with developed pore structure and high stability stand out.

[0004] As a renewable resource, lignin is the second most abundant biomass resource in the world. However, its complex structure and composition make it difficult to utilize lignin at a high value. Lignin has great potential in the preparation of multifunctional carbon materials due to its low cost, high aromaticity and high carbon content, and is expected to be widely used in the field of adsorption.

[0005] Chemical activation is a common method for preparing lignin-based sulfur-oxygen doped porous carbon adsorbents. It etches the internal structure of lignin to form pores, and can regulate the proportion of micropores, mesopores and macropores at the same time, thereby increasing the specific surface area and pore volume. In addition, chemical activation can introduce highly electronegative heteroatoms such as N, S, and O, and improve the adsorption effect by reducing the potential difference between the electron cloud density and the pollutant molecules. However, in order to achieve the purpose of doping atoms, traditional chemical activation is usually carried out by co-activation of activators and dopants, which increases the complexity of the preparation process. Therefore, it is crucial to achieve both activation and doping with one reagent. Studies have shown that doping S atoms with strong electronegativity into carbon materials can effectively increase the basicity of the carbon structure surface to more effectively adsorb cationic dyes. At the same time, its sulfur-containing functional group can often be used as an electron donor to improve the adsorption capacity through Lewis acid-base action. The O-containing functional group can further enhance the adsorption performance by strengthening hydrogen bonds and van der Waals forces. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the conventional adsorbents in the prior art, thereby providing a method for preparing a lignin-based sulfur-oxygen doped porous carbon adsorbent that can simultaneously achieve the two purposes of activation and doping to reduce the complexity of the chemical activation process, which can significantly simplify the preparation process and reduce labor intensity. In addition, the lignin-based sulfur-oxygen doped porous carbon adsorbent prepared by the preparation method of the present invention has greatly improved the adsorption capacity and removal rate of the methylene blue solution.

[0007] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.

[0008] The first aspect of the present invention provides a method for preparing a lignin-based sulfur-oxygen doped porous carbon adsorbent, comprising the following steps:

[0009] (1) mixing lignin and potassium thiosulfate and adding them into a ball mill for ball milling to prepare a coarse mixture;

[0010] (2) cooling the coarse mixture in step (1) to room temperature and then grinding it to obtain a lignin-based sulfur-oxygen doped porous carbon precursor;

[0011] (3) subjecting the lignin-based sulfur-oxygen doped porous carbon precursor in step (2) to a high-temperature carbonization activation treatment to obtain a lignin-based sulfur-oxygen doped porous carbon crude product;

[0012] (4) Grinding the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then washing and filtering, and drying the obtained product and further grinding it to obtain the obtained product.

[0013] Preferably, the lignin in step (1) is selected from one or more of alkali lignin, enzymatic lignin, lignin sulfonate, organic solvent lignin, dealkalized lignin, and sulfate lignin; more preferably, the lignin is selected from alkali lignin.

[0014] Preferably, in step (1), the mass ratio of lignin to potassium thiosulfate is 1:1-3; more preferably, the mass ratio of lignin to potassium thiosulfate is 1:2-2.5; most preferably, the mass ratio of lignin to potassium thiosulfate is 1:2.

[0015] Preferably, the ball mill in step (1) is selected from a zirconium oxide ball mill.

[0016] Preferably, the ball milling beads used in the ball milling in step (1) are selected from zirconia ball milling beads; more preferably, the diameter of the zirconia ball milling beads is 1-5 mm, for example, 2-4 mm; most preferably, the mass of the zirconia ball milling beads is 20-40% of the total mass of lignin and potassium thiosulfate.

[0017] Preferably, the ball milling speed in step (1) is 300-1000 rpm, and the time is 30-240 min; more preferably, the ball milling speed is 400-800 rpm, and the time is 60-180 min; most preferably, the ball milling speed is 600 rpm, and the time is 120 min.

[0018] Preferably, the lignin and potassium thiosulfate in step (1) may be optionally dried before mixing.

[0019] Preferably, the drying temperature is 50-100°C; more preferably, the drying temperature is 70°C.

[0020] Preferably, the heating rate of the high-temperature carbonization activation in step (3) is 5-15°C / min, the temperature is 500-1000°C, and the time is 30-240min; more preferably, the heating rate of the high-temperature carbonization activation is 8-12°C / min, the temperature is 600-900°C, and the time is 120min; most preferably, the heating rate of the high-temperature carbonization activation is 10°C / min, the temperature is 800°C, and the time is 120min.

[0021] Preferably, the high-temperature carbonization activation in step (3) is carried out under an inert gas atmosphere.

[0022] Preferably, the inert gas is selected from one or more of nitrogen, argon, helium and carbon dioxide; more preferably, the inert gas is selected from nitrogen.

[0023] Preferably, the lignin-based sulfur-oxygen-doped porous carbon precursor in step (3) can be optionally evenly spread in a container before being subjected to high-temperature carbonization activation treatment, and the height of the raw material after spreading does not exceed 1 / 3 of the internal height of the container.

[0024] Preferably, the washing in step (4) is selected from one or more of water washing, acid washing and alkali washing; more preferably, the washing is specifically: water washing, acid washing, alkali washing and water washing in sequence.

[0025] Preferably, the reagent used for the water washing is selected from one or more of distilled water, deionized water and ultrapure water.

[0026] Preferably, the reagent used for pickling is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid and acetic acid; more preferably, the reagent used for pickling is selected from hydrochloric acid; more preferably, the reagent used for pickling is selected from hydrochloric acid with a concentration of 1M.

[0027] Preferably, the reagent used for the alkali washing is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate; more preferably, the reagent used for the alkali washing is selected from sodium hydroxide; most preferably, the reagent used for the alkali washing is selected from sodium hydroxide with a concentration of 1M.

[0028] Preferably, the drying temperature in step (4) is 50-100°C and the time is 3-24h; more preferably, the drying temperature is 60-90°C and the time is 6-18h; most preferably, the drying temperature is 70°C and the time is 12h.

[0029] The second aspect of the present invention provides a lignin-based sulfur-oxygen-doped porous carbon adsorbent prepared according to the above preparation method.

[0030] The third aspect of the present invention provides the use of the lignin-based sulfur-oxygen-doped porous carbon adsorbent prepared according to the above preparation method in dye adsorption and supercapacitors.

[0031] The present invention uses lignin as a carbon source and potassium thiosulfate as a S, O dopant and activator, and proposes a new lignin activation technology. Lignin and K2S2O3 are mixed by ball milling at a specific mass ratio to improve the repeatability and stability of the carbonization activation process structure. Subsequently, carbonization and activation are carried out in a tubular furnace under a nitrogen gas flow, which can effectively inhibit the occurrence of mixed activation side reactions of the activator and the heteroatom dopant in traditional chemical activation, and realize one-step activation and doping to prepare porous carbon. During the carbonization process of the lignin-based sulfur-oxygen doped porous carbon precursor, on the one hand, under the high temperature environment of the tubular furnace, potassium thiosulfate interacts with lignin molecules to achieve the purpose of pore formation through gas production, and the sublimation of potassium atoms in potassium thiosulfate further etches and forms pores, thereby improving the material specific surface area and pore volume. On the other hand, potassium thiosulfate has rich sulfur and oxygen contents, and introduces rich sulfur-containing functional groups and oxygen-containing functional groups into porous carbon during the activation process. The doped sites can be used as adsorption active sites, and pore formation is conducive to exposing more active sites to participate in adsorption, thereby significantly enhancing its adsorption performance. The present invention has a simple preparation process and low equipment requirements, can effectively reduce production and preparation costs, and is suitable for industrial large-scale production.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] (1) The present invention utilizes potassium thiosulfate to activate lignin and form pores, and strictly controls the dosage ratio of lignin to potassium thiosulfate and the high-temperature carbonization activation temperature, thereby significantly increasing the specific surface area and pore volume of the material, which is beneficial for exposing more active sites to participate in the adsorption process.

[0034] (2) The present invention introduces sulfur and oxygen from potassium thiosulfate through co-activation of two raw materials, enriches the sulfur-containing functional groups and oxygen-containing functional groups in the lignin-based sulfur-oxygen-doped porous carbon skeleton, increases the surface active sites, and facilitates its adsorption reaction.

[0035] (3) The present invention directly utilizes waste lignin extracted from papermaking black liquor, and forms a carbon adsorbent with high specific surface area and rich heteroatom functional groups through activation, doping and carbonization, thereby making high-value use of industrial waste, effectively reducing the amount of papermaking waste liquor discharged in the industrial papermaking industry and reducing pollution to the environment.

[0036] (4) As a lignin-based sulfur-oxygen doped porous carbon adsorbent, the present invention exhibits excellent adsorption performance for methylene blue adsorption reaction, and its maximum adsorption capacity reaches 1122 mg / g. The comprehensive performance is significantly better than that of the same type of porous carbon adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The adsorption results of methylene blue by lignin-based sulfur-oxygen doped porous carbon adsorbents of Examples 1-5 and Comparative Examples 1-6 are shown.

[0038] Figure 2 The nitrogen adsorption / desorption and pore size distribution diagrams of the lignin-based sulfur-oxygen doped porous carbon adsorbents of Examples 1-4 at different activation temperatures; wherein (a) is a schematic diagram of the N2 adsorption-desorption isotherm results; and (b) is the pore size distribution of Examples 1-4.

[0039] Figure 3 Continuous adsorption curves of the lignin-based sulfur-oxygen-doped porous carbon adsorbent in Example 1 at different concentrations (a, b, c) and flow rates; wherein, dosage: 50 mg, flow rate: 1 mL / min, flow rate: 50 mL, concentration: 138, 236 and 350 mg / L; adsorption curves of Example 1 at different flow rates (b, d and e); dosage: 50 mg, flow rate: 50 mL, concentration: ≈240 mg / L, flow rate: 0.5, 1 and 2 mL / min.

[0040] Figure 4 The effects of different adsorption models of lignin-based sulfur-oxygen doped porous carbon adsorbent in Example 1; (a) 298K (b) 308K (c) 318K (dose: 10 mg, solution volume: 50 mL, time: 12 h); (d) constant K d Thermodynamic simulation equations for the distribution and adsorption temperature T; (e) The effect of contact time on the adsorption of MB in Example 1 at different initial concentrations; (f) Intraparticle diffusion model for the adsorption of MB in Example 1.

[0041] Figure 5 This is the CP curve of the lignin-based sulfur-oxygen doped porous carbon supercapacitor in Example 1.

[0042] Figure 6 This is the CV curve of the lignin-based sulfur-oxygen doped porous carbon supercapacitor in Example 1. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0045] Example 1

[0046] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0047] (1) 5 g of alkali lignin and 10 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in a 70° C. oven before mixing; the amount of zirconia ball mill beads added was 4.5 g; too few ball mill beads resulted in insufficient mixing of the two raw materials, while too many ball mill beads resulted in excessive collision and friction between the raw materials and the ball mill beads after the raw materials were fully mixed, resulting in excessive temperature in the ball mill, which was likely to cause premature reaction between the raw materials.

[0048] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0049] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat. If the spreading height is too high, it is easy for the inside and outside of the precursor powder to be heated unevenly, which increases the uncertainty of the preparation. Subsequently, it is placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a crude lignin-based sulfur-oxygen doped porous carbon.

[0050] (4) Grind the crude lignin-based sulfur-oxygen doped porous carbon product in step (3), then add ultrapure water to wash and filter; then use 1M hydrochloric acid to pickle and soak for 15 hours and filter. If the molar concentration of the pickling agent is too low, the impurities in the crude lignin-based sulfur-oxygen doped porous carbon product will not be fully removed. If the concentration is too high, it will cause corrosion and collapse of the carbon structure; then use 1M sodium hydroxide to alkaline wash and soak for 15 hours under ultrasonic conditions and filter to dissolve the sulfur that cannot be removed in the pickling step; finally, use ultrapure water to wash and filter, and dry at 70°C for 12 hours to obtain.

[0051] Example 2

[0052] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0053] (1) 5 g of alkali lignin and 10 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in an oven at 70° C. before mixing; the amount of zirconia ball mill beads added was 5 g.

[0054] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0055] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0056] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0057] Example 3

[0058] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0059] (1) 5 g of alkali lignin and 10 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in an oven at 70° C. before mixing; the amount of zirconia ball mill beads added was 5 g.

[0060] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0061] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0062] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0063] Example 4

[0064] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0065] (1) 5 g of alkali lignin and 10 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in an oven at 70° C. before mixing; the amount of zirconia ball mill beads added was 5 g.

[0066] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0067] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 900°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0068] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0069] Example 5

[0070] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0071] (1) 5 g of alkali lignin and 12.5 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm. The mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were placed in a 70° C. oven for sufficient drying before mixing; the amount of zirconia ball mill beads added was 5.5 g.

[0072] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0073] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0074] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0075] Comparative Example 1

[0076] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0077] (1) 5 g of alkali lignin and 5 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in an oven at 70°C before mixing; the amount of zirconia ball mill beads added was 3 g.

[0078] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0079] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0080] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0081] Comparative Example 2

[0082] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0083] (1) 5 g of alkali lignin and 7.5 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm. The mixture was placed in a vertical planetary ball mill and operated at 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were placed in a 70° C. oven for sufficient drying before mixing; the amount of zirconia ball mill beads added was 4 g.

[0084] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0085] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0086] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0087] Comparative Example 3

[0088] A lignin-based sulfur-oxygen doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0089] (1) 5 g of alkali lignin and 15 g of potassium thiosulfate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm, and the mixture was placed in a vertical planetary ball mill and operated at 600 rpm for 120 min to prepare a rough mixture, wherein the alkali lignin and potassium thiosulfate were pre-dried in a 70° C. oven before mixing; the amount of zirconia ball mill beads added was 6 g.

[0090] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based sulfur-oxygen doped porous carbon precursor.

[0091] (3) The lignin-based sulfur-oxygen doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with a height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based sulfur-oxygen doped porous carbon crude product.

[0092] (4) Grind the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for acid washing and soaking for 15 hours and filter; then use 1M sodium hydroxide for alkaline washing under ultrasonic conditions for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0093] Comparative Example 4

[0094] A lignin-based K2CO3-activated porous carbon adsorbent, the preparation method of which comprises the following steps:

[0095] (1) 5 g of alkali lignin and 10 g of potassium carbonate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm. The mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture; the amount of zirconia ball mill beads added was 5 g.

[0096] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based K2CO3-activated porous carbon precursor.

[0097] (3) The lignin-based K2CO3-activated porous carbon precursor in step (2) is evenly spread in a porcelain boat, with the height not exceeding 1 / 3 of the porcelain boat; then it is placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based K2CO3-activated porous carbon crude product.

[0098] (4) Grind the crude lignin-based K2CO3-activated porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for pickling and soaking for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0099] Comparative Example 5

[0100] A lignin-based KHCO3 activated porous carbon adsorbent, the preparation method of which comprises the following steps:

[0101] (1) 5 g of alkali lignin and 7.5 g of potassium bicarbonate were mixed and added to a zirconia ball mill, followed by adding zirconia ball mill beads with a diameter of 3 mm. The mixture was placed in a vertical planetary ball mill and operated at a speed of 600 rpm for 120 min to prepare a rough mixture; the amount of zirconia ball mill beads added was 4 g.

[0102] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based KHCO3-activated porous carbon precursor.

[0103] (3) The lignin-based KHCO3-activated porous carbon precursor in step (2) is evenly spread in a porcelain boat, with the height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a crude lignin-based KHCO3-activated porous carbon product.

[0104] (4) Grind the crude lignin-based KHCO3-activated porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for pickling and soaking for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0105] Comparative Example 6

[0106] A lignin-based KHCO3-activated sulfur-doped porous carbon adsorbent, the preparation method of which comprises the following steps:

[0107] (1) 5 g of alkali lignin, 7.5 g of potassium bicarbonate and 2.5 g of thiourea were mixed and added to a zirconia ball mill jar, followed by adding zirconia ball mill beads with a diameter of 3 mm, and placed in a vertical planetary ball mill mixer and operated at a speed of 600 rpm for 120 min to prepare a coarse mixture; the amount of zirconia ball mill beads added was 4 g.

[0108] (2) After the coarse mixture in step (1) is cooled to room temperature, the solid block is taken out and ground into powder to obtain a lignin-based KHCO3-activated sulfur-doped porous carbon precursor.

[0109] (3) The lignin-based KHCO3-activated sulfur-doped porous carbon precursor in step (2) is evenly spread in a porcelain boat, with the height not exceeding 1 / 3 of the porcelain boat; then placed in a tubular furnace and heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere for high-temperature carbonization activation treatment for 120 minutes to obtain a lignin-based KHCO3-activated sulfur-doped porous carbon crude product.

[0110] (4) Grind the crude lignin-based KHCO3-activated sulfur-doped porous carbon in step (3), then add ultrapure water for washing and filter; then use 1M hydrochloric acid for pickling and soaking for 15 hours and filter; finally, use ultrapure water for washing and filter, and dry at 70°C for 12 hours.

[0111] Verification Example 1

[0112] Take 10 mg of the lignin-based porous carbon adsorbent material prepared in Examples 1-5 and Comparative Examples 1-6 respectively for methylene blue (MB) static adsorption test to examine its adsorption performance. The specific steps are as follows: The methylene blue adsorption test is carried out in a constant temperature shaking shaker, a 1000 mg / L methylene blue solution is prepared, 10 mg of porous carbon adsorbent is weighed and added to a conical flask, and then 50 mL of methylene blue solution is added, and the mixture is continuously shaken at 120 rpm for 12 hours at 35 ° C, and then 50 μm of the adsorbed solution is taken out, and the methylene blue concentration is measured at 664 nm using a UV-visible photometer. The adsorption capacity q e (mg / g) is calculated according to the following formula:

[0113]

[0114] The adsorption results are shown in Table 1 and Figure 1 As shown. The results show that the carbon material obtained by activating lignin with only potassium carbonate or potassium bicarbonate in Comparative Examples 4 and 5 has limited adsorption performance, which is attributed to the limited effect of a single activator and the lack of heteroatom doping to improve the electronegativity of the carbon material. In Comparative Example 6, the doping of thiourea can increase the adsorption capacity of the carbon material for methylene blue to a certain extent, but the degree is still limited. Examples 1-5 and Comparative Examples 1-3 are explored from the two aspects of the mass ratio of the activator and the activation temperature. The results show that too much or too little activator is not conducive to the activation of lignin. When the mass ratio of lignin to potassium thiosulfate is 1:2-2.5, the adsorption performance of the adsorbent is significantly improved, and the optimal ratio is 1:2. Similarly, the carbonization activation temperature also has a significant effect on the adsorption performance of the adsorbent. Within a certain range, the adsorption activity of the adsorbent increases with the increase of temperature, and the optimal temperature range is 600-900°C.

[0115] Subsequently, in order to test the specific surface area, pore volume and pore size distribution of the carbon materials of Examples 1-4, the carbon materials of Examples 1-4 were subjected to BET tests, as shown in Tables 2 and Figure 2 The results show that Examples 1-4 present abundant specific surface area and pore volume, and the pore size distribution changes with the activation temperature. Figure 2 In (a), in the low-pressure stage of P / P0<0.01, the nitrogen adsorption of Examples 1-4 increased sharply to varying degrees, indicating that Examples 1-4 all have rich microporous structures. After P / P0>0.2, the adsorption of Examples 1-4 still increased, but the upward trend slowed down, and the slowing trend weakened with the increase of activation temperature. In the stage of 0.4<P / P0<1.0, Examples 1, 3 and 4 showed obvious hysteresis loops, indicating that the three have certain mesoporous structures. Figure 2 (b) It was found that K2S2O3 as an activator helps to enrich the micropore and mesopore distribution of carbon materials, among which the micropores of 1-2nm and the mesopores of 2-7nm are relatively dense. Compared with Example 2 and Example 3, Example 1 and Example 4 have larger specific surface area and pore volume, reaching 3301m 2 / g and 3134m 2 / g, 2.33cm 3 / g and 2.06cm 3 / g. Comparing Example 1 and Example 4, it is found that in addition to having a higher specific surface area and pore volume, Example 1 has a mesoporosity of 80%. This shows that the process conditions under Example 1 are suitable conditions for activation of K2S2O3 as an activator. Although Example 4 can obtain better adsorption performance than Example 1 at 900°C, based on comprehensive considerations such as the increase in temperature, the decrease in yield, the degree of improvement in adsorption effect, and the fact that Example 1 has a higher specific surface area and pore volume, the optimal carbonization activation temperature is 800°C.

[0116] Table 1 Methylene blue adsorption test results of Examples 1-5 and Comparative Examples 1-6

[0117]

[0118]

[0119] Table 2 BET pore size distribution of Examples 1-4

[0120]

[0121]

[0122] To further explore the adsorption removal rate under continuous conditions, adsorption experiments were performed for different starting concentrations (100, 200, 300 mg / L) and fluid flow rates (0.5, 1, 2 mL / min). 50 mg of the lignin-based porous carbon adsorbent material prepared in Example 1 was collected in a syringe filter, 50 mL of MB solution was added to the syringe, adsorbed at a specific flow rate at room temperature, and the adsorbed solution was collected regularly.

[0123]

[0124] Test results such as Figure 3 As shown. The results show that Example 1 has a high removal rate for MB at three different concentrations, and the removal rate stability only decreases by 0.05%, 0.12% and 0.1% respectively when 50mL MB solution is continuously adsorbed. On the one hand, the MB solution at a relatively high concentration has a higher mass transfer power during the flow process, which promotes the carbon material adsorbent of Example 1 to adsorb MB more effectively. On the other hand, at a higher MB concentration, the limited active sites of the carbon material adsorbent of Example 1 make it difficult for the purified solution to reach the level at a low MB concentration. Therefore, at C0≈236mg / L, the removal rate of the carbon material adsorbent of Example 1 is relatively higher than that of C0≈138mg / L and C0≈350mg / L, and the concentration of C0≈236mg / L was used in the subsequent flow rate test. In the flow rate experiment, it can be found that a lower flow rate concentration can achieve a higher removal efficiency, but the stability of its removal rate varies greatly, while the opposite is true for high flow rates. At low flow rates, the carbon material adsorbent of Example 1 can have a longer contact time with the MB solution, so the overall removal rate is higher. However, due to the good adsorption effect in the early stage, the limited active sites make the carbon material adsorbent in Example 1 saturated earlier, so that its removal rate changes greatly.

[0125] Verification Example 2

[0126] 10 mg of the adsorbent prepared in Example 1 was added to a flask, and then MB solutions (50 mL) of different concentrations (100-1000 mg / L) were prepared respectively, and adsorption was performed at three temperatures of 298 K, 308 K and 318 K. The equilibrium concentration and adsorption capacity were collected, and the Langmuir and Freundlich isotherm models were fitted. In addition, the data obtained in this experiment were used for thermodynamic parameter fitting. The Langmuir and Freundlich model equations are as follows.

[0127]

[0128] q e =K F C E 1 / n .

[0129] In addition, three concentrations of MB solutions of 600, 800, and 1000 mg / L were prepared, and different adsorption times (10-720 min) were studied, and pseudo-first-order kinetics and pseudo-second-order kinetics were fitted. In addition, the data obtained in this experiment were used to fit the intraparticle diffusion model. The pseudo-first-order kinetics and pseudo-second-order kinetics model equations are as follows.

[0130]

[0131] Among them, q e (mg / g) is the adsorption capacity at adsorption equilibrium, C0 (mg / L is the initial concentration of MB solution, C e is the MB concentration at equilibrium, V(L) is the volume of MB solution, m(g) is the mass of the carbon material adsorbent in Example 1, and q m (mg / g) is the maximum adsorption amount calculated by the Langmuir equation, n is the Freundlich index, K L , K F are the Langmuir and Freundlich constants, respectively. t is the theoretical adsorption capacity in adsorption kinetics. K1 and K2 are the rate constants in pseudo-first-order kinetics and pseudo-second-order kinetics, respectively.

[0132] The test results are shown in Table 3-5 and Figure 4 The results show that the carbon material adsorbent of Example 1 has a high fitting rate for the Langmuir isotherm model and the pseudo-second-order kinetic model, indicating that the adsorption process data of MB by the carbon material adsorbent of Example 1 is a monolayer adsorption, the number of active sites is limited and evenly distributed, and chemical adsorption occurs. Figure 4 (d) Thermodynamic results show that the adsorption process is an endothermic reaction. The adsorption reaction is spontaneous and its spontaneity increases with increasing temperature. Figure 4 (f) shows the adsorption kinetics q t With t 0.5The relationship between the surface diffusion and the adsorption rate of the carbon material adsorbent of Example 1 is shown in Figure 1. After linear fitting, three segments with different slopes appear, representing the three stages of surface diffusion, mesopore diffusion and micropore diffusion in sequence. The slopes K1, K2 and K3 are the adsorption rates of each stage. It is observed that K1>K2>K3, indicating that the diffusion effect weakens as the adsorption process proceeds. The fitting straight line of the surface diffusion stage does not pass through the origin, indicating that intra-particle diffusion is not the only step that controls the adsorption rate. At this stage, a large number of MB molecules in the solution diffuse to the surface of the carbon material adsorbent of Example 1, and MB combines with the active sites exposed on the surface of the carbon material adsorbent of Example 1 for adsorption. In the mesopore diffusion stage, due to its developed and complex pore structure, the mass transfer resistance in the MB diffusion process becomes larger, and the adsorption efficiency is slowed down, but it still has a certain adsorption effect. In the micropore stage, the pore size is too small, making it difficult for MB molecules to flow effectively, so they are adsorbed in the micropores in the form of pore filling. At this stage, the adsorption effect is limited, indicating that the micropore diffusion stage is the rate-limiting step in the adsorption process of the carbon material adsorbent of Example 1.

[0133] Table 3 Langmuir and Freundlich model fitting parameters for Example 1

[0134]

[0135] Table 4 Thermodynamic fitting parameters of Example 1

[0136]

[0137]

[0138] Table 5 Pseudo-first-order kinetics and pseudo-second-order kinetics parameters of Example 1

[0139]

[0140] Verification Example 3

[0141] To prepare the working electrode, 80 wt% of the carbon material prepared in Example 1, 10 wt% of PTFE and 10 wt% of carbon black were uniformly mixed in ethanol and coated on a 0.8 cm 2 The carbon paper was dried at 85°C overnight. In the three-electrode battery test, 1M KOH was used as the electrolyte, mercuric oxide was used as the reference electrode, and the platinum electrode was used as the counter electrode to detect the specific capacitance of the lignin-based sulfur-oxygen doped porous carbon in Example 1 under different conditions and the CP curve and CV curve of the supercapacitor. The test results are shown in Table 6 and Figure 5-6As shown. The results show that the carbon material supercapacitor of Example 1 has a specific capacitance of 250F / g at a current of 1A / g in 1M KOH. The CV curve is rectangular in the voltage window of -0.1-0.1V and the scanning rate range of 50-1000mV / s, which proves its excellent rate performance and fast kinetic behavior.

[0142] Table 6 Specific capacitance table of Example 1 under different conditions

[0143]

[0144] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a lignin-based sulfur-oxygen doped porous carbon adsorbent, characterized in that: The steps include: (1) mixing lignin and potassium thiosulfate and adding them into a ball mill for ball milling to prepare a coarse mixture; (2) cooling the coarse mixture in step (1) to room temperature and then grinding it to obtain a lignin-based sulfur-oxygen doped porous carbon precursor; (3) subjecting the lignin-based sulfur-oxygen doped porous carbon precursor in step (2) to a high-temperature carbonization activation treatment to obtain a lignin-based sulfur-oxygen doped porous carbon crude product; (4) Grinding the crude lignin-based sulfur-oxygen-doped porous carbon in step (3), then washing and filtering, and drying the obtained product and further grinding it to obtain the obtained product.

2. The preparation method according to claim 1, characterized in that: The mass ratio of lignin to potassium thiosulfate in step (1) is 1:1-3.

3. The preparation method according to claim 1, characterized in that: The ball milling speed in step (1) is 300-1000 rpm, and the time is 30-240 min.

4. The preparation method according to claim 1, characterized in that: The lignin in step (1) is selected from one or more of alkali lignin, enzymatic lignin, lignin sulfonate, organic solvent lignin, dealkalized lignin, and sulfate lignin.

5. The preparation method according to claim 1, characterized in that: The heating rate of the high temperature carbonization activation in step (3) is 5-15°C / min, the temperature is 500-1000°C, and the time is 30-240min.

6. The preparation method according to claim 1, characterized in that: The high-temperature carbonization activation in step (3) is carried out under an inert gas atmosphere.

7. The preparation method according to claim 1, characterized in that: The washing in step (4) is selected from one or more of water washing, acid washing and alkaline washing.

8. The preparation method according to claim 1, characterized in that: The drying temperature in step (4) is 50-100° C. and the drying time is 3-24 hours.

9. The lignin-based sulfur-oxygen doped porous carbon adsorbent prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the lignin-based sulfur-oxygen doped porous carbon adsorbent prepared according to any one of claims 1 to 8 in dye adsorption and supercapacitors.

Citation Information

Patent Citations

  • Sulfur-doped biomass hard carbon material as well as preparation method and application thereof

    CN113912039A

  • Preparation method of sulfur-doped porous carbon-based carbon dioxide adsorbent

    CN117361529A

  • Preparation method of nitrogen and sulfur double-doped graded porous activated carbon

    CN118771373A